The Welfare States of Hungary's Fidesz and Poland's Law and Justice: Explaining the Surprisingly Divergent Trajectories - Jakub Tomášek (London School of Economics and Political Science (LSE), European Institute, 2023)
The Fidesz-led government in Hungary and the Law and Justice-led government in Poland have shared important similarities since assuming power in the last decade, from party ideology to selective engagement with collective bargaining institutions. Yet, their approach to the welfare state has markedly contrasted, with Poland expanding and Hungary retrenching welfare provision. This paper uses the method of difference to address this conundrum. The power resources approach, if appropriately clarified and widened, helps us identify an independent variable of difference: the balance of power between labour and capital. Empirical support is found for two hypotheses. First, Hungarian business elites exert higher influence over welfare state policymaking than Polish elites. Second, the Hungarian government can stay in office more safely without satisfying its voters' welfare state preferences. The findings imply a continuing relevance of the power resources approach for understanding crosscountry social policy differences, even in countries with comparatively weak unions and left parties.
Keywords: 330; welfare state; power resources; populist radical-right parties; Hungary; Poland